Aplikasi Pakan Konsentrat Berbasis Bahan Lokal untuk Meningkatkan Pertumbuhan dan Kualitas Karkas Sapi - Khasrad Khasrad; Arnim Arnim; R.W.S. Ningrat; Rusdimansyah Rusdimansyah (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2011)
The Pesisir cattle are indigenous West Sumatera cattle. Their quality needs to be improved since they can live in local environment with sufficiently available feed resources. A research has been done to study the effects of feeding level and fattening period to the growth and the carcass characteristics of the Pesisir cattle. This research was designed by using block design with three blocks. The first factor was two levels of feeding, i.e: A1 = 50 % concentrate + 50 % ammoniated rice straw, A2 = 75 % concentrate + 25 % ammoniated rice straw. The second was time period of fattening, i.e: B1 = 3 months and B2 = 4 months. The results showed that there was no interaction between the level of feeding and fattening period to the growth, percentage of carcass, the back fat thickness and the rib eye area of the Pesisir cattle (P> 0.05). The higher of concentrate percentage, the higher the growth of the cattle, the thicker the back fat and the wider the rib eye area will be (P<0.05). Similarly, the longer the fattening, the higher the percentage of carcass, the thicker the back fat and the wider rib eye area will be.